COMPARATIVE LINGUISTIC ANALYSIS OF PROVERBS ABOUT DOMESTIC ANIMALS IN UZBEK AND ENGLISH LANGUAGES (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the rich cultural diversity of proverbs from both Uzbek and English, with a particular emphasis on proverbs concerning domestic animals. Proverbs offer particular perspectives into the principles, beliefs, and cultural peculiarities of a community since they are statements of collective knowledge. Through an examination of a particular selection of proverbs regarding domestic animals in these languages, this article looks at how these proverbs represent the traits, behaviors and symbolism of domestic animals, comparing and contrasting their depictions.